Religion, Science and Morality: Concentric circles or mutually exclusive? - Singapore Management University (Institutional Knowledge at Singapore Management University, 2012)
It was termed a debate on religion, science and morality, and two academics – one a self-declared atheist and the other, a Christian – squared off to give their takes on two questions that have plagued many minds: Can atheists be truly moral, and can a scientist be truly religious?